Aparicion y significado de la moganita en fas rocas de la sílice: una revision - Bustillo, M.A. (Journal of Iberian Geology, 2002)
Moganite (formerly SiOrG) is a novel monoclinic silica polymorph and is a widespread distribution component in microcrystalline silica rocks. The identification of moganite in the presence of a large proportion of quartz is difficult by microscopy or other usual mineralogical methods. Rietveld refmements of powder X-ray diffraction or a position-sensitive detector system allows identification and quantification by XRD. Raman and NMR analysis also provides a measure of moganite content and the micro-Raman permits their spatial variation in the microcrystalline textures to be known. The results obtained indicate that moganite occurs as a metastable phase that transforms to quartz, if sufficient time or a change in ambient conditions are produced. The general diagenetic sequence of the silica rocks used at the present (opal A ~ opal CT ~ quartz) must be revised because moganite is part of the opaline maturation sequence. Moganite is abundant in arid environments, this is probably due to the lack of water available to support the dissolution of moganite and the simultaneous precipitation of quartz. More data about the moganite in evaporitic environments may determine special kinds of sulphate or alkaline environments. Moganite is absent in weathered and hydrothermally altered silica rocks.